DYNAMICS OF FAMILY RESILIENCE TO ECONOMIC CRISIS: English - Aulia, Nida Rivdah; Setiawati, Farida Agus; Nurhayati, Siti Rohmah (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Economic crises can affect various aspects of family life, including finances, interpersonal relationships, and mental health. This research aims to explore family resilience in the face of the economic crisis with a focus on internal family dynamics and the adaptation strategies applied. The research method employed is qualitative, utilizing a case study approach. The study included 3 participants who had experienced an economic crisis, and they were interviewed using semi-structured interviews. This research analysis uses descriptive analysis. Data collection techniques using interviews and observations. The results showed that the family belief system was the main driver in facing difficulties. Adaptive strategies, such as strict budget management and open discussions on financial matters, proved effective in maintaining the financial stability and well-being of family members. Communication patterns used during the crisis also played an important role, with families that used open communication tending to be better able to cope with conflict and stress. This study concludes that family resilience in the face of economic crisis is the result of a combination of strong belief systems, effective adaptation strategies, and open communication patterns that support cooperation and solidarity between family members. The findings provide important insights for development programs and policies that can help families cope with the economic crisis.